The relationship between technical skills, perceived tactical skills and self-regulatory skills in youth elite tennis players - Kolman, N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Technical skills have been demonstrated crucial for tennis performance. Ball speed and accuracy are usually considered the two most important components of technique in tennis (Landlinger et al., 2012). These components are not only crucial for current tennis performance, but also vital for future tennis success in youth tennis players. Tactical skills and the perceptions thereof have been suggested to influence these skills, and self-regulatory skills may be beneficial for technical skills in various tactical situations (Kolman et al.,2019; Kolman et al., submitted). However, the relationship between technical skills in a tennis-specific situation and perceived tactical skills has not been investigated yet, and also the association with self-regulatory skills is unknown. Therefore, the purpose of this study is to explore the relationship between technical skills in various tactical situations, perceived tactical skills and self-regulatory skills among 21 youth elite tennis players (13 males, 8 females; age range 12-18 years).